2021
DOI: 10.1016/j.heliyon.2021.e06041
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of calcium-binding proteins expression and cisplatin chemosensitivity by calcium chelation in human breast cancer MCF-7 cells

Abstract: Cisplatin (CDDP) is currently one of the most effective FDA-approved treatments for breast cancer. Previous studies have shown that CDDP-induced cell death in human breast cancer (MCF-7) cells is associated with disruption of calcium homeostasis. However, whether the sensitivity of breast cancer cells to cisplatin is associated with dysregulation of the expression of calcium-binding proteins (CaBPs) remains unknown. In this study, we evaluated the effect of the intracellular calcium chelator (BAPTA-AM) on viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…To date, several studies have shown an interaction between Ca 2+ and ROS: 57,58 maintaining the normal Ca 2+ level of the cell is conducive to the stability of the redox state in the cell, consequently ensuring the normal operation of mitochondria and other organelles. 59…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several studies have shown an interaction between Ca 2+ and ROS: 57,58 maintaining the normal Ca 2+ level of the cell is conducive to the stability of the redox state in the cell, consequently ensuring the normal operation of mitochondria and other organelles. 59…”
Section: Resultsmentioning
confidence: 99%
“…To date, several studies have shown an interaction between Ca 2+ and ROS: 57,58 maintaining the normal Ca 2+ level of the cell is conducive to the stability of the redox state in the cell, consequently ensuring the normal operation of mitochondria and other organelles. 59 Low concentrations of AsA, ZnCl 2 , and BAPTA-AM could inhibit the oxidative stress induced by Cd, restore cell viability, and alleviate the cytotoxicity of Cd (Fig. 9).…”
Section: Effect Of Bapta-am On Mcf-7 Cellsmentioning
confidence: 92%
“…Similarly, lipid-regulating enzymes ANXA1, S100A8, and FABP5 are co-regulated in a network with ApoE and APP in response to sepsis [ 40 ]. The known calcium-binding proteins (CALML5, S100A8, S100A14) modulate cancer therapeutics and survival [ 41 , 42 ]. Several candidates, especially TXN, S100A8, ANXA1 and LGALS7 are strongly associated with oxygen radical processes, a key ferroptosis trigger.…”
Section: Resultsmentioning
confidence: 99%
“… 68 , 96 This is interesting because gap junction communication plays an important role in calcium (Ca 2+ ) signaling whereas cisplatin uptake, along with its cytotoxicity and chemosensitivity, are dependent on the cytosolic calcium concentration. 97 This claim can be supported by the lower cisplatin and IC 50 concentrations required to exert significant anticancer activity in MDA-MB-231 and MDA-MB-468 cells apart from apoptotic induction and the limited metastatic ability via the upregulation of differentiation and the downregulation of CSC makers. However, the mechanisms by which oleamide can induce connexins to mediate cisplatin chemosensitivity remain unclear and need to be investigated further.…”
Section: Discussionmentioning
confidence: 99%